Comparison of increasing the width and thickness of keratinized gingiva using two methods of connective tissue graft and graft by plasma-enriched collagen in patients who are candidates for gingival grafts: A pilot study - Hengameh Khosropanah; Ali Dehghani; Samira Esmaelzadeh (Isfahan University of Medical Sciences, 2013)
Introduction: Nowadays the necessity of the existence of a certain width of keratinized gingiva is emphasized upon to maintain periodontal health and prevent soft tissue recession around teeth and dental implants. This study was carried out to compare two gingival graft procedures including connective tissue graft and graft with a combination of collagen sponge with platelet-rich plasma and platelet-rich fibrin to increase the width and thickness of keratinized gingiva.Materials and Methods: In this clinical trial 8 patients with bilateral inadequate width (≤ 2 mm) and thickness (≤ 1 mm) of keratinized gingiva on the buccal aspect of single-rooted teeth were selected. On the control side, connective tissue graft and on the test side, graft by combination of stypro+PRP+PRF were performed. After surgery, the measurements were repeated at 1, 2 and 3 months. Data was analyzed by Wilcoxon's test to compare the 2 groups and Friedman's test was used for comparisons within each group with SPSS 15 (α = 0.05).Results: After 3 months there were no differences between test and control groups in relation to the width of keratinized (p value = 0.317), attached gingival (p value = 0.527), thickness of the graft (p value = 0.05) and thickness of the keratinized layer (p value = 1).Conclusion: It appears the new approach for gingival augmentation used in this study may be a proper substitute for autogenous gingival grafts. Key words: Collagen, Connective tissue, Gingiva, Plasma